Transaction Efficiency as a Mediator in the Relationship between QRIS Adoption and MSME Profitability: Evidence from Trading MSMEs in Palangka Raya - Nahdya Irsa; Roby Sambung; Ronni Haga; Dhina Sri Widyaningsih (Jurnal Investasi Islam, 2026)
This study aims to examine the effect of Quick Response Code Indonesian Standard (QRIS) adoption on the profitability of trading micro, small, and medium enterprises (MSMEs) in Palangka Raya City, with transaction efficiency positioned as a mediating variable, given the persistent gap between the rapid growth of QRIS merchants and the uncertain financial benefit felt by traders who bear the Merchant Discount Rate (MDR) cost. A quantitative associative-causal design was employed using a questionnaire survey distributed to 100 trading MSME respondents selected through purposive sampling across Jekan Raya, Pahandut, and Sebangau Districts, and the data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The measurement model met all validity and reliability criteria, and bootstrapping results show that QRIS adoption has a positive and significant effect on transaction efficiency and on profitability; transaction efficiency significantly affects profitability; and transaction efficiency partially and complementarily mediates the QRIS-profitability relationship, with all four hypotheses supported at the 95% confidence level. These findings imply that the profitability gain from QRIS is not automatic; it is optimized when MSME actors actively use QRIS features to build genuine operational efficiency, so that policy support should shift from merely expanding merchant registration toward strengthening MSME capacity to utilize digital cash-management features.